Sustainable Tourism Development: the Adaptation and Resilience of the Rural Communities in (the Tourist Villages of) Karimunjawa, Central Java - Setiawan, Budi; Rijanta, R; Baiquni, Muhammad (Universitas Muhammadiyah Surakarta, 2017)
From 2009 to 2015, the growth of tourism in the tourist villages (desa wisata) of Karimunjawa underwent rapid progress. However, the level of poverty in Karimunjawa remained high. Nevertheless, the involvement of rural people in the sustainable development of tourism has received only limited discussion. Therefore, this article discusses the rural communitiesâ adaptation and resilience in Karimunjawa with the support of sustainable development planning in tourist villages. It covers the background of sustainable development, the elements of the communitiesâ adaptive capacity and resilience, and the role of the regional government. Empirical evidence of variations in the capacity to respond to changes of socioeconomic and ecological environments due to tourism development is presented. In addition, a case study is used in this article to describe how the people learned from their experience, knowledge, and past efforts. To obtain the necessary information, in-depth interviews were conducted with a number of key informants in the tourist villages of Karimunjawa, which were selected via purposive and snowball sampling. The results of the research show that social resilience will increase among those communities that are capable of accessing flexible social networks. These social networks are practical tools that open up the dissemination of new information and knowledge. This is a key element for a stronger process of transformation. Furthermore, communities that have capital and financial access as well as skills will also be capable of adaptation to the transformation process.